2023
DOI: 10.7554/elife.83874
|View full text |Cite
|
Sign up to set email alerts
|

The Dantu blood group prevents parasite growth in vivo: Evidence from a controlled human malaria infection study

Abstract: Background:The long co-evolution of Homo sapiens and Plasmodium falciparum has resulted in the selection of numerous human genetic variants that confer an advantage against severe malaria and death. One such variant is the Dantu blood group antigen, which is associated with 74% protection against severe and complicated P. falciparum malaria infections in homozygous individuals, similar to that provided by the sickle haemoglobin allele (HbS). Recent in vitro studies suggest that Dantu exerts this protection by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Lastly, we investigated copy number variation at the cluster of glycophorin genes that determine the MNS blood group. A complex structural rearrangement affecting both GYPA and GYPB and encoding the Dantu antigen has been associated with protection from severe P. falciparum malaria but is common only in coastal east African populations 47,79,80 . Applying a Hidden Markov Model to infer copy number from coverage data across this locus (including a mappability filter as in Leffler et al 2017 47 ) and looking at tag SNPs, we identified one Omani and one Qatari individual carrying the Dantu structural variant (Supplementary Figure 5; Supplementary Table 5), suggesting it has likely spread to the southern Arabian Peninsula through east African admixture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, we investigated copy number variation at the cluster of glycophorin genes that determine the MNS blood group. A complex structural rearrangement affecting both GYPA and GYPB and encoding the Dantu antigen has been associated with protection from severe P. falciparum malaria but is common only in coastal east African populations 47,79,80 . Applying a Hidden Markov Model to infer copy number from coverage data across this locus (including a mappability filter as in Leffler et al 2017 47 ) and looking at tag SNPs, we identified one Omani and one Qatari individual carrying the Dantu structural variant (Supplementary Figure 5; Supplementary Table 5), suggesting it has likely spread to the southern Arabian Peninsula through east African admixture.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous different SNVs that cause G6PD deficiency found in populations throughout the world 72 as well as beta-thalassemias, which are also at relatively low frequency potentially due to balancing selection. We identify the P. falciparum -associated Dantu structural variant (SV), which has only been reported at appreciable frequency in coastal East Africa 47,79,80 . However, it was carried by a single Omani individual who had a high proportion of African ancestry genome-wide, suggesting it may result from more recent admixture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if there were strong causality, this correlation is not expected to be absolute, as there are many other determinants of parasitaemia in the peripheral blood at a given time, and some community infections at low parasitaemia could potentially go on to become high parasitaemia infection leading to hospitalisation. The direction of causality also remains to be established, as variation in the in vivo blood-stage environment during infection, including differences in host erythrocytes, iron availability and inflammatory immune responses [20-22], may stimulate parasites to adjust their intrinsic growth rate phenotypes which then persist in culture.…”
Section: Discussionmentioning
confidence: 99%